Desarrollo de antivenenos basados en anticuerpos de yema de huevo contra veneno de Bothrops alternatus - Leiva, Carlos Leónidas (2021)
The administration of antivenoms based on heterologous polyclonal antibodies\nis the only effective tool available to treat snakebite envenomings and, therefore, is a\npriority for Public Health. Traditionally, these medicines are produced in horses,\nhowever, an alternative to this production is based on the use of egg yolk antibodies\n(IgY-Technology) due to their economic, ethical and productive advantages. In this\nthesis, IgY-based antivenoms were produced, characterized and evaluated against the\nvenom of Bothrops alternatus. Different variables were evaluated for the\nimmunization of laying hens and the serological response curve was determined by\nELISA. Egg yolk extracts were produced and their protein content was analyzed by\nBradford, ELISA and HPLC-ESI-MS/MS. The antivenoms were able to recognize and\nneutralize up to 68.74 ?g venom/mg antivenom, as well as the hemorrhagic activity of\nthe bothropic venom in a murine model. Likewise, the immunogenicity of the\nantivenom was evaluated. IgY-Technology could enable the production of effective and\naffordable antivenoms that meet the urgent needs of many countries where\nconventional manufacture is unable to provide enough availability of antivenoms.